A1.2 High Throughput analysis of IGG fab glycosylation reveals differences between RA-patients and healthy controls during pregnancy and after delivery. (31st January 2014) - Bondt, Albert; Rombouts, Yoann; Hazes, Johanna M W; Wuhrer, Manfred; Dolhain, Radboud J E M
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is known to improve during pregnancy, and flare after delivery [1].1] This correlates with changes of the N-glycosylation pattern in the constant region (Fc) of immunoglobulin (Ig) G [2, 3].2, 3] In addition to Fc-glycosylation, 15-25% of IgG antigen binding fragments (Fab) carry N-glycans [4].4] These Fab-linked N-glycans have been suggested to influence affinity to antigen and antibody half-life whereas their role in pregnancy and RA remains unclear [4, 5].4, 5] Our objective was to explore IgG Fab glycosylation of RA patients compared to healthy controls during pregnancy and after delivery, and compare it to Fc glycosylation. Materials and Methods: Sera were collected preferably before conception (T1, only RA-patients), at three times during pregnancy (T2-4) and three times after delivery (T5-7) from RA-patients (n = 28) and healthy controls (n = 29) participating in the PARA-study, a prospective cohort study on the effect of pregnancy on RA. IgG was affinity purified from 5 µL serum. Using IdeS enzyme IgG was cleaved in two ½ Fc portions and a F(ab')2 portion. Fc and F(ab')2 were separated, and glycans were released, followed by automated MALDI-TOF measurement to establish the levels as well as patterns of glycosylation. Results: At all six time points during pregnancy and after delivery, Fab portions of RA-patients show a significant higher level of neutral glycans compared to healthy controls (T2-T5 p<0.0001; T6 p<0.05), which occurs at the expense of galactosylated and sialylated species. Consequently, lower levels of disialylated glycans are observed in RA-patients compared to controls (p<0.001; except for T7: p = 0.28). Relative to Fc-glycans, Fab-linked N-glycans of RA-patients exhibit higher levels of galactosylation (Fab: 86% (SD 9%); Fc: 54% (9%)), sialylation (Fab: 50% (4%); Fc: 16% (4%)) and bisection (Fab: 48% (7%); Fc: 14% (3%)). Similar results were obtained for controls. In addition, comparison of the 3 rd trimester and pre-conception state showed changes for bisection (48 to 40%; p<0.005) and fucosylation (63 to 57%; p<0.05). After delivery bisection was found to change significantly in patients (42 to 47%; p<0.005). No other pregnancy related changes in glycosylation were observed for Fab-linked N-glycans. Conclusions: IgG Fab glycosylation is different for RA patients compared to healthy controls. As for Fc glycosylation, lower levels of galactosylation and sialylation can be observed on the Fab of RA patients. Furthermore, glycosylation of the Fab portion differs from Fc glycosylation. In contrast to glycosylation of the Fc, Fab glycosylation shows less pregnancy-associated changes over time.